Experimental check of possibility of research of repeated inclusion of the open gas generator in the water environment; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Goldaev S. V. Sergey Vasilievich; Barsukov V. Vitaly; Basalaev S. Sergey; Minkova N. Natalya (2017, 2017)
Title screen